Fuzzy and ant colony optimization based trust evaluation system for a cloud environment - Sivakami, R.; Vincent Antony Kumar, A. (International Journal of Engineering and Technology, 2018)
From consumersâ€™ perspective, knowing the trust level of cloud service providers with maximum accuracy is often considered as a difficult task in cloud computing for security related arguments. The proposed trust evaluation system adopts the well-defined parameters for evalu-ating the trustworthiness of cloud service providers. This system employs fuzzy theory integrated with ant colony optimization. Initially, the believability index of each consumer is calculated. Then the fuzzy inference system is constructed for measuring the trust index of a cloud service provider. Several experiments were conducted and the results were analyzed to understand the impact of the four parameters on trust index. Then the system is applied for the developed cloud computing environment to show its efficiency. Experimental results demonstrate that the proposed system can give an effective solution to trust evaluation problems in open environments.Â